AI-MEDIATED SCAFFOLDING IN CIVIC ENGLISH: A COMPARATIVE PEDAGOGICAL PERSPECTIVE FROM INDONESIAN AND UZBEK HIGHER EDUCATION - Sangkala, Ismail; Haq, Muhammad Zia ul; Tohirovna, Abdullayeva Lola (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores the integration of Generative Artificial Intelligence (Gen-AI) as a scaffolding tool for mastering English for Specific Purposes (ESP) within the field of Civic Education. By adopting a cross-regional perspective, the research examines how AI facilitates technical vocabulary acquisition and grammatical competence—specifically regarding Modal Verbs—among pre-service teachers in Indonesia and Uzbekistan, two nations currently undergoing significant digital transformations in their educational sectors. The research utilizes a descriptive-evaluative approach, integrating a pedagogical needs analysis from an Indonesian cohort with a comparative policy review of Uzbekistan’s recent foreign language reforms. Data were gathered through structured surveys focusing on linguistic barriers in